Engineering Smart Stimuli-Responsive Carriers for Precision Drug Delivery: Current Trends and Future Outlook - Salve, Yash Manoj; Lote, Sukeshini Bharat; Dandekar, Mayur Rajeshwar; Mirzapure, Isha Anil (International Journal of Pharmaceutical Investigation, 2026)
Stimuli-Responsive Drug Delivery Systems (SRDDS), also regarded as smart” drug delivery systems, have emerged as a vital element of precision pharmaceutics, with the ability of a spatiotemporally controlled therapeutic release for patients individualized physiology or outside-served stimuli. These systems utilize endogenous stimuli (pH, redox gradients, enzyme activity) or external stimuli (temperature, light, magnetic fields, and ultrasound) to activate a drug at the disease site, enhance the therapeutic effect, and decrease body toxicity. In this sense, we provide an updated summary with critical perspectives on the recent advancements regarding SRDDS, emphasizing the essential new ones in terms of materials, nanocarrier proxies, and design strategies that lead to the new generations of SRDDS remaining studied in depth and well characterized in preclinical animal models. We classify SRDDS based on the type of stimulus and highlight their individual and combination for advanced disease treatment, including cancers, neurodegenerative diseases, infectious diseases, and chronic inflammation. We also outline the regulatory, manufacturing, and translational challenges that are current barriers to clinical implementation and approaches to overcome them. Lastly, we present the current directions in this area, including multi-stimuli responsive systems, hybridization with biosensing technologies, and prospective applications for mRNA and gene delivery. In this review, we summarize and delineate various opportunities offered by SRDDS for next-generation precision therapeutics.
Keywords: Stimuli-responsive drug delivery; Smart therapeutics; Nanocarriers; Controlled release; Precision pharmaceutics; Biosensors; Multi-responsive systems.